2019
DOI: 10.3390/ph12030102
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase Inhibitory Activity of Cycloartane-Type Triterpenes Isolated from Indonesian Stingless Bee Propolis and Their Structure–Activity Relationship

Abstract: This study reports on the antioxidant activity and α-glucosidase inhibitory activity of five cycloartane-type triterpenes isolated from Indonesian stingless bee (Tetragonula sapiens Cockerell) propolis and their structure–activity relationships. The structure of the triterpenes was determined to include mangiferolic acid (1), Cycloartenol (2), ambonic acid (3), mangiferonic acid (4), and ambolic acid (5). The inhibitory test results of all isolated triterpenes against α-glucosidase showed a high potential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
(64 reference statements)
3
21
1
1
Order By: Relevance
“…Cytoprotection and beta cell proliferation are important targets for the treatment of type II diabetes. Plant derived compounds (including terpenoids) are reported to show beta cell protection from hyperglycemia and amelioration of diabetic complications [38,[49][50][51][52].…”
Section: Plos Onementioning
confidence: 99%
“…Cytoprotection and beta cell proliferation are important targets for the treatment of type II diabetes. Plant derived compounds (including terpenoids) are reported to show beta cell protection from hyperglycemia and amelioration of diabetic complications [38,[49][50][51][52].…”
Section: Plos Onementioning
confidence: 99%
“…The study of Pujirahayu et al, 2019 tested the inhibitory effect of several triterpenes from propolis (cycloartenol, ambonic acid, mangiferonic acid, and ambolic acid) on alpha-glucosidase. The results showed that mangiferonic acid from propolis had the strongest inhibitory effect on alpha-glucosidase with an IC50 of 3.46 µM/mL ( Figure 1 ) [ 86 ].…”
Section: Mechanistic Studies With Active Constituents From Propolis In Metabolic Diseasesmentioning
confidence: 99%
“…It was reported that SBP is rich with cycloartane compounds in high enough levels to produce high antioxidant activity, which resulted in inhibitory activity against yeast α-glucosidase [ 87 ]. In addition to the antioxidant properties shown by inhibition of inflammatory enzymes [ 87 ], SBP also decreased the mutagenesis in yeast cells ( Saccharomyces cerevisiae ) [ 96 ]. In the same study, SBP extracts were more effective against gram-positive bacteria than gram-negative bacteria [ 96 ].…”
Section: Stingless Bee Propolis (Sbp)mentioning
confidence: 99%